Formulation Optimization of Erythromycin Solid Lipid Nanocarrier Using Response Surface Methodology. (18th June 2014) - Sahu, Anil Kumar; Kumar, Tekeshwar; Jain, Vishal
Abstract : In present work response surface methodology (RSM) using the miscellaneous design model was used to optimize formulations of erythromycin solid lipid nanocarriers (ERY-SLN). Two-factor three level factorial design was considered for optimization. There were three parameters, drug entrapment efficiency (EE), drug loading (DL) percentage, and mean particle size of ERY-SLN, considered for investigating the optimal formulation with respect to two independent variables, including lipid concentration ( X 1 ) and surfactant : cosurfactant ratio ( X 2 ). The result showed that the optimal ERY-SLN was composed of lipid concentration ( X 1 ) 15 mg/mL and surfactant : cosurfactant ratio ( X 2 ) 1 : 1 with %EE of 88.40 ± 2.09%, DL of 29.46 ± 0.69%, mean particle size of 153.21 ± 2.31 nm, polydispersity index (PDI) of 0.026 ± 0.008, and zeta potential value of −15.18 ± (−5.53) mV. DSC and TEM study showed that there was no chemical interaction between ERY and lipid (GMS) and the ERY-SLN particles are nonspherical, respectively. The drug release experiments exhibited a sustained release over during 24 h, up to 66.26 ± 2.83%. Accelerated stability studies showed that there was no significant change occurring in the responses after storage condition for a total period of 3 months.